2019
DOI: 10.1016/j.clim.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

SLAMF6 in health and disease: Implications for therapeutic targeting

Abstract: Effective immune responses develop after a well-orchestrated series of events that include recognition, immune cell interactions and activation/inhibition of signaling pathways. The signaling lymphocyte activation molecule family (SLAMF) of cell surface receptors, which consists of nine transmembrane proteins (SLAMF1-9) expressed at different levels, are involved in viral and bacterial recognition, serve as co-stimulatory molecules at immune synapses, and modulate myeloid and lymphocyte development. SLAMF rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 299 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, Yigit et al . has shown that the administration of SLAMF6 antibodies in combination with the BTK kinase inhibitor Ibrutinib has a positive effect on depleting leukemia cells from mice [33]. Given the aforementioned studies we have decided to proceed with SLAMF6 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Yigit et al . has shown that the administration of SLAMF6 antibodies in combination with the BTK kinase inhibitor Ibrutinib has a positive effect on depleting leukemia cells from mice [33]. Given the aforementioned studies we have decided to proceed with SLAMF6 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…SLAMF receptor functions are controlled by the SLAM-associated protein (SAP) family of adaptors, comprising SAP, EAT-2, and ERT, which either block the recruitment of inhibitory phosphatases (like SHP-1 or SHP-2) or directly activate signaling pathways. These interactions dictate the activation or inhibitory nature of the SLAMF receptors upon engagement (41, 42). Here, we found that EAT-2 was highly expressed in CAL-1 cells, stable upon infection with Salmonella and when SLAMF7 or SLAMF8 were down-regulated (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…This immune checkpoint molecule has been shown to control CD8 + T cells and NK cells ( Lee et al, 2017 ). In addition, SLAMF6 is another negative regulator of CD8 + T cell response ( Yigit et al, 2019a ; Yigit et al, 2019b ) up-regulated during osteoclastogenesis. Thus, osteoclasts not only support myeloma cell growth, but they also impede immune responses through several highly expressed negative regulators of immune response including, but not limited to, MMP9, MMP14, B7-H3, PD-L1, and PD-L2.…”
Section: Discussionmentioning
confidence: 99%